BIOTECHNOLOGICAL APPLICATIONS AND POTENTIAL USES OF THE MUSHROOM TRAMESTES VERSICOLOR - CÓRDOBA M., Ketty A.; RÍOS H., Alicia (Vitae, 2012)
The use of products obtained from fungi (particularly mushrooms) has increased lately due to their broad applicability in different scientific and industrial fields. The genus Trametes comprises a group of white rot producing ligninolytic fungi, with medicinal properties, biotechnological importance and environmental applications. One of the most potentially useful species is T. versicolor, formerly known as Coriolus versicolor or Polyporus versicolor. Also known as Yun Zhi in China, is a fungus species belonging to the class Basidiomycetes, which has a widespread application as medicinal mushroom, and is also consumed as food and tea infusion. It also produces extracellular enzymes such as laccases, manganese peroxidases, lignin peroxidases and H2O2 producing oxidases. These enzymes are capable of degrading such complex compounds as lignin, as well as certain industrial contaminants. T. versicolor is one of the first higher fungi to be used in the production of an approved medicine. In effect, polysaccharides like Polysaccharide Krestin and Polysaccharide Peptide obtained from the liquid fermentation of its mycelium, exhibit anticarcinogenic properties, and are therefore used for preparing several pharmaceutical products. Both polysaccharides are highly effective in treatments against cancer. The present review addresses certain properties of T. versicolor, as well as its potential applications in different biotechnological fields.